The application of the bamboo dancing type cooperative learning model in improving students’ critical thinking skills in social studies learning class v SDN Jati 4 - Diniyah, Salwa; Ridwan, Ita Rustiati (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
This research aims to improve students’ critical thinking skills by using a bamboo dancing type cooperative learning model in IPAS Class V learning of SDN Jati 4. This research is a classroom action research with the Kemmis & Tagart model. The research was carried out in the odd semester of the 2024/2025 school year in two cycles of each cycle of one meeting. The subject of this study is 25 students in grade V of SDN Jati 4. The results of the study showed that students’ critical thinking skills improved after applying the bamboo dancing type cooperative learning model to IPAS Class V learning of SDN Jati 4. The learning outcomes at the time of the pre-program, the average student score was 65.24 for students who reached KKM there were 11 students (44%) and students who did not reach KKM there were 14 students (56%). In the first cycle, an increase in critical thinking skills was obtained, the average grade score was 72.4 with the graduation of students who reached the KKM as many as 19 students (76%) and students who did not graduate as many as 6 students (24%), it can be seen that there was an increase in the average score from pre-cycle to cycle I of 7.16. In the second cycle, the results increased again with an average score of 80.6, as many as 21 students (84%) passed and as many as 4 students (16%) did not pass. Thus, there was an increase in the average value from cycle I to cycle II by 8.2.